The Use of Panoramic Radiography for Condyle Shape Detection on Menopausal Periods in Dentistry Radiology Installation – Dental and Oral Hospital of Universitas Sumatera Utara: Penggunaan Radiografi Panoramik untuk Mendeteksi Bentuk Kondilus pada Menopause di Instalasi Radiologi Kedokteran Gigi – Rumah Sakit Gigi dan Mulut Universitas Sumatera Utara - Manja, Cek Dara; Rizky Gusti MS; Sheilla Suhaila Matondang (TALENTA, 2021)
Panoramic radiographs can be used to detect temporomandibular morphology and condylar changes. This study shape-determines the female condyle in perimenopausal and postmenopausal using panoramic radiography. It used an observational survey technique with a sample of 80 people, consisting of 40 perimenopausal aged between 20 and 29, and 40 postmenopausal females aged over 52. The results on the perimenopausal condyle process obtained a round shape of 43.7%, an angle of 32.5%, and a pointed shape of 23.7%. Furthermore, the shape of the condylar process in postmenopause is 37.5% pointed, 30% angled, 25% round, and 7.5% flat. Data were analyzed using the Chi-Square test with a significance value of p<0.05. The results showed that changes in the size and shape of the condyles occur with age. There is a significant difference in the condyle shape between perimenopausal and postmenopausal periods.